EUROMOD baseline report - Silvia De Poli; Celia Gil-Bermejo Lazo; Chrysa Leventi; Sofia Maier; Andrea Papini; Mattia Ricci; Hannes Serruys; Vanda Almeida; Michael Christl; Hugo Cruces; Paola De Agostini; Klaus Grünberger; et al. (European Commission, Joint Research Centre (JRC), 2023)
This report provides a selection of baseline results and headline indicators from the latest public version (I5.0+) of EUROMOD, the tax-benefit microsimulation model for the EU. We begin by presenting indicators for income inequality and at-risk-of-poverty. We then provide a comparative decomposition of the redistributive effect of the tax-benefit systems across the EU. We study how different Member States achieve various degrees of redistribution through different combinations of progressivity and size of their tax-benefit systems. We then analyse various work incentive indicators both at the intensive and the extensive margin, discussing how effective marginal rates of taxation and replacement rates vary across countries. The report also describes the way EUROMOD can be used to simulate economic shocks leading to labour market transition through the LMA (Labour Market Adjustment) add-on. We illustrate this by simulating the impact of the COVID-19 pandemic and the cushioning effect of policy measures taken by EU Member States. Finally, we present the evolution of the income distribution over the post-financial crisis decade and we compare living standards across EU countries at the top and the bottom of the income distribution.
Keywords: 330; Mikrosimulation; Steuer; Öffentliche Sozialleistungen; Armut; Soziale Ungleichheit; EU-Staaten